The Effects of Moringa Oleifera Leaves Extract on Histological Changes Induced in the Distal Convoluted Tubules of the Kidneys of Adult Albino Rats by Bisphenol - Ejaz, Rabia; Umar, Muhammad; Majeed, Aisha; Shami, Amber; Mir, Amaidah; Butt, Hammad Ahmed (Journal of Postgraduate Medical Institute, 2025)
Objective: To evaluate the protective effects of Moringa oleifera leaves extract (MOLE) against BPA-induced histological changes in the DCTs of adult albino rat kidneys. Methodology: This experimental study was conducted at animal house Postgraduate Medical Institute (PGMI), Lahore from March, 2019 to April, 2020. This study involved 30 male adult albino rats divided into three groups: control group, BPA-exposed, and MOLE-treated plus BPA-exposed. The BPA group received 50 mg/kg BPA orally, while the MOLE-treated group received 400 mg/kg MOLE alongside BPA. Kidney tissues were examined histologically using hematoxylin and eosin staining. Results: BPA exposure led to notable histological alterations in the DCTs, such as tubular dilation, epithelial cell degeneration, and inflammatory infiltration. In contrast, co-administration of MOLE significantly reduced these changes. The protective effect of MOLE is likely due to its antioxidant components, such as polyphenols and flavonoids, which mitigate oxidative stress and inflammation. Conclusion: Moringa oleifera leaves extract showed protective potential against BPA-induced renal damage in rats, highlighting its possible therapeutic role in preventing kidney damage caused by environmental toxins.